Employee stock options schemes in Singapore : pricing and accounting issues and disclosures. - Lee, Mike Chiang Hai. (2009)
This study looked into the major accounting issues involved in accounting for ESOs and proposed appropriate accounting treatment for the ESOs using ED40 and RAP1A as a theoretical framework.